Sequencia didática aplicada ao ensino médio para estudo da difração da luz utilizando materiais alternativos - FERREIRA , Jose Alvino Sousa (2020)
For high school students “Physics is difficult”, and when treated without context and clarity, the beauty of science goes unnoticed by the student. The present work aims to assist High School Physics teachers by producing a Didactic Sequence using alternative materials for the study of Diffraction of Light, which is sometimes little addressed by the Physics books selected by the National High School Textbook Program, and it is mentioned within the wave teaching of the second year of high school, sometimes in a less comprehensive way. On the other hand, the choice of building a Didactic Sequence was due to its own identification with the teaching approach and its application started with a questionnaire, then the development of a Concept Map to assess and level the previous knowledge. necessary for the development of the theme, then a class was applied through dialogue and exposure of the Diffraction theme and after this action, a presentation of works was developed, while the evaluation was carried out during its stages of execution and finally, a satisfaction survey to assess the methodology used during the application of the Didactic Sequence. The proposal described in this work is based on the principles of Significant Learning by David Ausubel and Critical Significant Learning by Marco Antonio Moreira culminating in: assembly and application of experiments in diffraction of light by a hair; diffraction net with discarded CD; production of posters and video recording using cell phone as an aid in teaching-learning in Diffraction. The application of research and development of the experiments was carried out with students from two third year classes in a high school, located in São Luís, capital of the State of Maranhão. For the collection of analytical data, the use of tests and annotations of records on the application of the work was considered. The quantitative and qualitative results obtained have guaranteed us some success in meaningful learning. The acceptance of the Didactic Sequence obtained good results during qualitative evaluation since the teaching approach constituted a different modality in the transmission of the content.